Identity and Interpretation of Public Artworks: A Challenge to Intentionalism - Baldini, Andrea (Kultura-Społeczeństwo-Edukacja, 2015)
This paper explores whether MT and IT apply to public artworks. In particular, it discusses whether a public artwork can acquire through time a property that cannot possibly accord with the artist's intentions, and consequently, whether an interpretation that attributes that "new" property to that public artwork can be legitimate. It also clarifies when an artwork is public and introduces the example of a public artwork that seems to have acquired a property at odds with the artist's intentions. It discusses and argues that Carroll's intentionalist account of conversation is insufficient. Conversations, like public artworks, possess perlocutionary features that, at least sometimes, cannot be explained on intentionalist grounds.